Employment subsidies, informal economy and women's transition into work in a depressed area: Evidence from a matching approach - Manuela Deidda; Adriana Di Liberto; Marta Foddi; Giovanni Sulis (IZA Journal of Labor Policy, 2015)
We analyze the effects of an ALMP for disadvantaged workers implemented in a depressed area of Italy. Using propensity-score matching, we find that a) the employment subsidy had a positive effect for participants on both the probability of finding a job and income, b) the outcome of the policy was more positive for women, and c) the program was more effective for older and less-educated female workers. Using data on previous contacts between workers and firms and on informal channels for job search activity, we ultimately explore the role of the program in promoting the transition from informal to salaried employment.
Keywords: C14; C83; J64; J16; 330; Employment subsidies; Female labor-force participation; Evaluation; Informal economy